OP0336 Role of systemic inflammation associated with rheumatoid arthritis in the glucose and lipid metabolism: humans, cia mouse model and in vitro studies. (15th June 2017) - Rosa, I Arias de la; Rodriguez-Cuenca, S; Jimenez-Gomez, Y; Ruiz-Limon, P; Perez-Sanchez, C; Abalos, MC; Cecchi, I; Calvo, J; Guzman, R; Malagon, M; Collantes, E; Vidal-Puig, A; et al.
Abstract : Background: Rheumatoid arthritis (RA) patients are at higher risk for insulin resistance (IR). The association between RA and IR, and its role on the different characteristics of the disease, such as duration and activity have not been well defined. In addition, there is a gap of knowledge regarding the link between systemic/local inflammation and insulin sensitivity and lipid metabolism in RA patients. Objectives: To explore the effects of the inflammation on the glucose and lipid metabolism in the RA context, following three strategies: RA patients, collagen induced arthritis (CIA) mouse model and in vitro treatment of 3T3L1 adipocytes. Methods: Human study: 150 RA patients and 40 healthy donors were included. IR was quantified using the homeostatic model assessment of IR (HOMA-IR). Mouse model: 20 CB57J/BL mice were used; 5 mice were used as non-diseased group, and 15 were used in CIA modelling: sorted in low and high activity of the disease based on the number of inflamed digits depending on the duration of the disease. Plasma, leukocytes, skeletal muscle, liver and adipose tissue were collected. Treatment of adipocytes with serum from RA patients: 3T3L1 adipocytes were treated with serum 10% of RA patients and healthy donors for 24h. The expression of genes and proteins involved in inflammation, lipid metabolism and insulin signalling was analysed in all the tissues and cells. Results: Percentages of obesity, hypertension, atherogenic risk, metabolic syndrome and insulin resistance were significantly increased in the RA group. Although mean time of evolution was 7 years, no association between IR and the duration of the disease was found. Levels of HOMA-IR significantly correlated with DAS28 and C-reactive protein levels, suggesting that systemic inflammation might lead to the development of insulin resistance. In mice, the induction of arthritis promoted an alteration of the expression of genes involved in inflammation as well as lipid metabolism and insulin signalling in all the metabolic tissues and leukocytes, pointing out to an increase in lipolysis, decrease in adipogenesis and lipid accumulation and induction of IR. These results were recapitulated after treatment of adipocytes with serum from RA patients with high disease activity. Conclusions: 1) IR was closely associated with an increase in disease activity and systemic inflammation in RA patients. 2) Induction of arthritis in mice promoted an increase in inflammation markers in skeletal muscle, adipose tissue and leukocytes, and a reduction of genes involved in lipid uptake and storage, generating an insulin resistance state in those tissues. 3) The inflammatory components in RA serum induced lypolisis, reduced adipogenesis, and increase inflammation and insulin resistance in adipocytes 3T3L1. In sum, our results suggest that chronic inflammation associated with RA might directly impact relevant metabolic tissues, altering glucose and lipid homeostasis and favouring the development of insulin resistance. Acknowledgements: Funded by ISCIII-FIS (CP15/00158), PI2013/0191, RD16/0012/0015 and Roche Pharma S.A. Disclosure of Interest: None declared